Bridging Tourism Growth and Environmental Impact: An Empirical Analysis of CO2 Emissions in Sri Lanka - Dilrukshi, P.H.N.; Maheswaranathan, S. (Department of Economics, University of Colombo, 2025)
Tourism significantly contributes to economic growth, job creation, and generates foreign exchange earnings. However, energy consumption from transportation is a significant factor in the adverse environmental effects of tourism. Consequently, this research seeks to examine both short-term and long-term impacts of tourism on carbon dioxide (CO₂) emissions in Sri Lanka utilizing the annual data from 1990 to 2022, by employing Autoregressive Distributed Lag (ARDL) method. In this study, CO₂ emission is employed as the dependent variable while tourism arrivals, foreign direct investment (FDI), and gross domestic product (GDP) are considered as the independent variables. The findings revealed that existence of a significant strong long-term correlation between tourism arrivals, GDP, FDI and CO2 emissions from transport. Further, the findings confirmed that tourism has a strong and significant positive impact on CO₂ emission. Furthermore, Diagnostic assessments confirm the model's precision, and the Error Correction Model (ECM) shows that around 21.4% of the imbalance from the prior year is rectified in the current year, indicating a moderate rate of adjustment towards the long-term equilibrium. These findings emphasize the importance of sustainable tourism policies and cleaner technologies to harmonize economic advantages with environmental sustainability.
Keywords: Tourism; Economic Growth; Foreign Direct Investment; Environmental Sustainability; Transport Emissions